ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI INDUSTRI KECIL MENENGAH MAKANAN OLAHAN RENDANG TELUR DI KOTA PAYAKUMBUH SUMATERA BARAT ( STUDI KASUS : IKM RENDANG DI KAMPUNG RENDANG ) - Tri Komala Zelly; Jahrizal Jahrizal; Eka Armas Pailis (Jurnal Ekonomi, 2017)
Village rendang in payakumbuh city west sumatera , based on the formulation ,the formulation of the problem in this study is whether capital, labor and raw materials affect the production of rendang egg in the village rendang in payakumbuh city west sumatera. The purpose of this study was to investigate and analyze the influence of capital, labor , and raw materials to the amount of production of industrial enterprises in the rendang egg in the village rendang in payakumbuh city west sumatera. To menaganalis data using SPSS version 20.0 soft ware.Based on the results of tests performed by t test on each - each variable it can be concluded that the morally ( 4,320 ) and raw materials ( 6,595 ) significantly affects the production of industrial enterprises variable rendang egg, while the labor variable ( 0,006 ) positive affect and not significantly affect the production rendang telur industry . simultaneous test ( F test ) of capital , labor and raw materials have an influence on the production of industrial enterprise rendang egg in the village rendang. The amount R2 of 0.990 means that 99 percent of the production of industrial enterprises rendang egg can be explained by the independent variables ( capital labor and raw materials ) , and the remaining 1 percent is explained by other variables outside the model.